The behaviour management toolkit : avoiding exclusion at school - Parry-Mitchell, Chris (Sage, 2012)
Based on her successful work across a range of schools, this book consists of 10 sessions that make up a programme to help students who are at risk of exclusion. Each session has detailed facilitator notes and accompanying worksheets on the CD-Rom. The young people learn how to think, communicate, behave and relate to each other and other people in more useful ways. The book offers: - content that works for schools, Pupil Referral Units and any setting working with young people on behaviour management; - advice on dealing with common pitfalls and difficult scenarios; - guidance on how to work with parents and carers to help them understand how they can reinforce the approach at home; - activities that work with the 10 to 18 age range. Everything in this book has been tried and tested with young people who are at risk within their school settings, and for most of them it has been a turning point in their lives. Chris Parry-Mitchell is a teacher and freelance consultant based in Lancashire.